Historia Manon Lescaut i kawalera des Grieux - Prevost, abbe, 1697-1763.; Prevost, abbe, 1697-1763. (Warszawa : Wydawn. Polskiego Towarzystwa Wydawcow Ksiazek, 1987)
The classic love story of a country lass who meets and falls in love with a nobleman.
Translation of: Histoire du chevalier des Grieux et de Manon Lescaut.